The use of Malaysian English in Robert Raymer’s short stories / Melyza Pakianatham - Pakianatham, Melyza (2013)
This study is an attempt to categorize and describe the use of Malaysian English by a native English speaker who has lived in Malaysia for over 20 years. This person is an expatriate who has been actively involved in contributing to Malaysian literature, particularly in the area of creative writing. Two books written by Robert Raymer were used for the purpose of this study. A total of 16 short stories were analyzed using theoretical frameworks by Baskaran (2005). There was a total of 41 words and phrases that were used as data for the analysis according to the theoretical frameworks. This study will focus on the presence of words in these four categories and in the categories outlined by Baskaran (2005). There are two main categories used in the framework presented by Baskaran (2005). These two categories are Local Language Referents and Standard English Lexicalization. The sub-categories under Local Language Referents are Institutionalized Concepts, Emotional and Cultural Loading, Semantic Restriction, Cultural and Culinary Terms, Hyponymous Collocation and Campus or Student Coinages. The sub-categories under Standard English Lexicalization are Polysemic Variation, Semantic Variation, Informalization, Formalization, Directional Reversal and College Colloquialism. Robert Raymer’s view is used to triangulate the data and hence answer the last research question.